Dragons at Crumbling Castle : and other tales - Pratchett, Terry (Clarion Books/Houghton Mifflin Harcourt, 2015)
An illustrated collection of fourteen short stories featuring dragons and wizards, councilors and mayors, an adventurous tortoise and a monster in a lake, along with plenty of pointy hats and a few magic spells, written when the author was a teenaged newspaper reporter.